THE ESSENCE OF NEW NEWS MEDIA IN CHINA - Xu W. (Strategies of Sustainable Development: Social, Law and External-economic Aspects, 2024)
the article examines the essence of new news media in China, their role in the formation of public opinion and the development of information space. This article analyses the influence of new media on the society and culture of China, as well as their transformation in the conditions of modern information space. Special attention is paid to social networks and their use for news dissemination, formation of public opinion and interaction between people.
Keywords: Китай; интернет; социальные сети; Internet; China; media; новости; social networks; медиа-средства; новые медиа-средства; new media; news